Inside the Nation of Islam: By Vibert L. White, Jr. (Gainesville, FL: Uni versity Press of Florida, 2001. 256 pages.) (American Journal of Islam and Society, 2003)
The author, who embraced the teachings of Louis Farrakhan's revampedNation of Islam (NOI) in the late I 970s to find solutions to America's raceproblems, left disillusioned in the mid-1990s. What he witnessed as hepassed through the organization's rank and file compelled him to compilehis experiences to give others a clearer understanding of the Nation's originsas well as its role concerning the issues facing African-Americans.Inside the Nation of Islam is divided into I I chapters and contains aforeword by Mike Wallace an epilogue by the author, extensive notes, abibliography, and an index. Also included are several photographs thatillustrate White's extensive involvement in the NOLWith a brief overview of African-American history prior to the NOI'screation, chapters 1 and 2 touch on the Harlem Renaissance, the origin ofthe Jim Crow laws, and the mass exodus of African-Americans from theSouth to the North. With the fall of similar resistance movements, theNOJ stepped in to address the bitter disillusionment that many of themexperienced upon their arrival in the North ...